ONE PARAMETER COMPOSITE SEMIGROUPS OF LINIER BOUNDED OPERATORS ON STRONG OPERATOR TOPOLOGY OF SCHATTEN CLASS C - Hassan, Samir Kasim (MAGISTRA, 2011)
The object of the paper is to disxuss when ____, 0<t<Y is in the Schatte class Cp, 0<P<Y. for semigroups on a Bannach space of linier bounded operators on IIilbert space, and the problem of being Cp in is more interesting than of begin compact.